Labour Market Effects of Non-tariff Measures: A Computable General Equilibrium for the Food Processing Sector in Malaysia - Yew V.S.H.; Al-Amin A.Q.; Devadason E.S. (Springer, 2023)
computable general equilibrium analysis; economic impact; employment; food processing; labor market; tariff structure; wage; Malaysia